Focus Study on Motivation and Entrepreneur Intention: A Literature Review from Scopus Database - Arika, Deki; Mulyadi, Hari; Nuryanti, B Lena (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
This literature review investigates the relationship between motivation and entrepreneurial intention based on data sourced from the Scopus database. Entrepreneurship plays a critical role in economic development and innovation; thus, understanding the motivations behind entrepreneurial intentions is essential. This study systematically reviews 15 relevant documents retrieved using the keywords